Effect of Moral Distress on Decision Making among Nurses in Intensive Care Units - Murtadha Kudhair Al-Turfi, Mohammed Baqer Al-Jubouri (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Moral distress, as one of the most important issues in the nursing profession, can negatively affect the healthcare system Objectives: To examine the effect of moral distress on decision making. Methodology: A descriptive cross-sectional study a non-probability sampling method was used and a total sample collected was (126) ICU nurses Result: Moral distress among ICUs nurses were moderate and decision making was good Conclusion: Although nurses in ICUs perceive good decision making but suffered from moderate MD which affected their decision making. MD is still an important issue that nurses may face in ICUs Conclusion: Although nurses in ICUs perceive good decision making but suffered from moderate MD which affected their decision making. MD is still an important issue that nurses may face in ICUs